STUDIES ON PREPARATION OF Fe(III)/TiO2 BY SOL-GEL METHOD - Linda J Kusumawardani; Yulian Syahputri (Universitas Pakuan, 2019)
In this study, Fe/TiO2 powder was synthesized by sol-gel method using mixture of Titanium Tetraisopropoxide (TTIP) as precursor and FeCl3 as iron source of 10% (w/w). The Fe/TiO2 powder was calcined at 500 °C for 1 hour. The sample of Fe/TiO2 was characterized using FTIR anad DRS measurements. FTIR analysis showed that Fe was successfully doped on TiO2 and then DRS analysis proved that the visible light was absorbed by Fe/TiO2 with its band gap energy up to 2.3 eV